Pengaruh Project Based Learning dengan Pendekatan STEAM Terhadap Kemampuan Berpikir Kritis pada Pembelajaran Online di SMK Negeri 12 Malang - Sulastri Sulastri; Gita Putri Cahyani (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Critical thinking skills can be grown with a project based learning model with a STEAM approach. The purpose of this study was to determine the effect of Project Based Learning with the STEAM approach on critical thinking skills in online learning in accounting vocational schools. This research was conducted at SMKN 12 Malang class X. The research subjects involved 72 students. This study uses a quasi-experimental design in the form of Noneequivalent Control Group Design. The data collection technique used a test sheet in the form of an essay to collect ten items. The data analysis technique used independent sample t-Test analysis with the help of the SPSS application. The results showed that there were differences in the ability to think critically of students before and before getting treatment-based learning with the STEAM approach in online learning of service company financial statement materials. The critical thinking ability of students has increased significantly.